Referendum, response, and consequences for Sudan : the game between Juba and Khartoum - Elbadawi, Ibrahim 1984- (Policy research working paper, 2008)
"This paper presents a game theory model of the strategic interaction between Khartoum and Juba leading up to the referendum on Sudan's partition in 2011. The findings show that excessive militarization and brinksmanship is a rational response for both actors, neither of which can credibly commit to lower levels of military spending under the current status quo. This militarization is often at the expense of health and education expenditures, suggesting that the opportunity cost of militarization is foregone economic development. These credibility issues might be resolved by democratization, increased transparency, reduction of information asymmetries, and efforts to promote economic and political cooperation. The paper explores these devices, demonstrating how they can contribute to Pareto preferred outcomes in equilibrium. The authors characterize the military expenditure associated with the commitment problem experienced by both sides, estimate its costs from data for Sudan, and identify the opportunity cost of foregone development implied by continued, excessive, and unsustainable militarization. "--World Bank web site